A patient with severe hypoxia secondary to a large iatrogenic pulmonary artery to pulmonary vein fistula. (13th October 2014) - Diab, Khalil; Cucci, Anthony; Kukreja, Sandeep; Gupta, Rajat
Abstract : Pulmonary arteriovenous malformations are uncommon communications between the pulmonary arteries and veins, most commonly associated with hereditary haemorrhagic telangiectasia. They can also be associated with a variety of other conditions, and can be single or multiple. We present a case of a female patient with a history of coronary artery bypass grafting and mitral valve repair, who presented to the hospital with severe hypoxia. She was found to have a large pulmonary artery to superior pulmonary vein fistula that was successfully repaired using a septal occluder. To our knowledge, this is the first case of a large pulmonary artery to superior pulmonary vein fistula following mitral valve repair.